A practical combination method for wind-induced responses of high-rise buildings: Based on the correlation of extremes. (February 2022) - Pan, Xiaowang; Qu, Wenzhong; Zou, Lianghao; Xu, Guoji; Song, Jie
Abstract: This study proposes a practical three-dimensional combination method for wind-induced responses of high-rise buildings. Five high-rise buildings with different side ratios are considered, where the base shears in two translational directions and base torques of each model are measured by the high-frequency force balance technique. The wind-induced dynamic responses are then calculated based on the measurement. The wind-induced extreme response along one direction and the simultaneously observed wind-induced responses along the other two directions are systematically analyzed, through which the combination factors are determined from a probability view. The factors are then validated by comparing with those specified in several proceeding international codes and standards. The effects of the resonant component, building side ratio, and building surroundings on the combination of wind-induced responses are investigated. The results show that the correlation of the extremes is considerably different from the correlation of time histories. Generally speaking, neglecting the resonant component will underestimate the combination factors. The building side ratio has substantial influence on the combination factor. In the end, the proposed method is employed to calculate combination factors of an actual high-rise building to verify its application in engineering practice.